PENGARUH VARIASI RASIO ALKALI AKTIVATOR TERHADAP HILANG PIJAR DAN KONSISTENSI NORMAL SEMEN GEOPOLIMER BERBASIS TANAH NAPA KABUPATEN LINTAU - Fauzi, Muhammad (journal of residu, 2019)
Geopolymer is inorganic polymeric material which are formed by activating of having in abudance of alumina silica with alkali hydroxide solution or alkali silicate at room temperature or higher. One of the material that contain is Napa Soil. Based on XRF analysis of Mawardi (2015) the Napa Soil had a contain SiO2 dan Al2O3is very high with percentage 63,20% dan 16,55%, it can be used as based material at fabrication of geopolymer cement. In this study testing of lossof ignation (loi) and normal consistency of geopolymer cement with variations in alkali activator ratioNa2SiO3/NaOH 1, 1.5, 2, 2.5. Based on the results of the study, the optimum levels of loi and insoluble parts were obtained at a ratios 2.5, namely 6.63% and 23.69%. In soil-based geopolymer cement, the level of loi is higher than ordinary cement based on SNI because the SiO2 content in geopolymer cement is very high. While for normal consistency the amount water required meets the SNI standard.